1975
DOI: 10.1017/s0043174500062743
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Glyphosate on Johnsongrass

Abstract: Glyphosate [(N-phosphonomethyl) glycine] was evaluated for three years as a foliar herbicide for the control of johnsongrass [Sorghum halepense (L.) Pers.]. In the greenhouse, maximum rhizome kill resulted from foliar applications of glyphosate at 1.12 to 2.24 kg/ha. In several field studies, plowing from 4 to 21 days following glyphosate application had little effect on johnsongrass control; plowing within 0.5 hr following glyphosate application resulted in less control than when plowing was delayed for 12 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…Regrowth occurred following summer harvest each season in most plots, and substantial regrowth occurred in 2009 and 2010 in the plots harvested in 2008 and 2009, respectively (data not shown). Similar observations of regrowth following control efforts were also made in experiments with johnsongrass (Parochetti et al 1975), wirestem muhly (Lingenfelter and Curran 2007), common reed (Ailstock et al 2001;Derr 2008a;Rensburg 1996), reed canarygrass (Annen et al 2005), and giant reed (Spencer et al 2008). These observations support the hypothesis that control of this perennial, rhizomatous grass will likely require efforts over more than one growing season.…”
Section: Field Experiments With Established M 3 Giganteus Standssupporting
confidence: 73%
See 1 more Smart Citation
“…Regrowth occurred following summer harvest each season in most plots, and substantial regrowth occurred in 2009 and 2010 in the plots harvested in 2008 and 2009, respectively (data not shown). Similar observations of regrowth following control efforts were also made in experiments with johnsongrass (Parochetti et al 1975), wirestem muhly (Lingenfelter and Curran 2007), common reed (Ailstock et al 2001;Derr 2008a;Rensburg 1996), reed canarygrass (Annen et al 2005), and giant reed (Spencer et al 2008). These observations support the hypothesis that control of this perennial, rhizomatous grass will likely require efforts over more than one growing season.…”
Section: Field Experiments With Established M 3 Giganteus Standssupporting
confidence: 73%
“…rhizomes were effectively controlled (, 90%) with disking 10 times prior to planting agronomic crops (McWhorter and Hartwig 1965). Parochetti et al (1975) reported glyphosate at 1.1 to 3.4 kg ae ha 21 fb moldboard plowing 12 to 14 d later provided the best control of johnsongrass. Glenn et al (1986) applied fluazifop-p-butyl at 0.3 and 0.6 kg ai ha 21 , sethoxydim at 0.3 and 0.4 kg ai ha 21 , and glyphosate at 33% v/v in conventional tillage and no-till fields and found that all treatments provided good control of johnsongrass.…”
mentioning
confidence: 99%
“…Dinitroaniline herbicides give acceptable control of seedling and rhizomatous S. halepense; however, a 2-year programme involving incorporation and high rates of herbicide is required (McWhorter, 1977). Foliar applications of glyphosate to 5. halepense at or near the reproductive stage of growth has provided excel-lent control of 5. halepense (Parochetti, Wilson & Burt, 1975;Banks & Santelmann, 1977;Jeffery, English &Connell, 1981), but glyphosate must be directed at the S. halepense with special application techniques to avoid injury if a crop is present.…”
Section: Introductionmentioning
confidence: 99%
“…Another efficient way to kill the two grasses was with the aid of glyphosate, which was very efficient against both Bermuda grass and Johnsongrass. This is in accordance with reports in literature (Arenstein, 1973;Parochetti, Wilson & Burt, 1975). When mechanical cultivation between the rows was satisfactory, as in Aviel, perennial grasses along the rows disappeared after 3 years of treatment with the most potential herbicides, and treatments were discontinued.…”
Section: Discussionmentioning
confidence: 99%